2018
DOI: 10.1007/s10517-018-4045-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoxetine and Potential Antidepressant 8-Trifluoromethyl 1,2,3,4,5-Benzopentathiepin-6-Amine Hydrochloride (TC-2153) on Behavior of Danio rerio Fish in the Novel Tank Test and Brain Content of Biogenic Amines and Their Metabolites

Abstract: We compared the effect of a new potential antidepressant 8-trifluoromethyl 1,2,3,4,5-benzopentathiepine-6-amine hydrochloride (TC-2153) and classical antidepressant fluoxetine in a dose of 0.25 mg/liter on the behavior of Danio rerio in the "novel tank" test and content of biogenic amines and their metabolites in the brain. Fluoxetine alone and TC-2153 alone significantly increased the time spent in the upper part of the tank and insignificantly reduced motor activity. Combined exposure of fishes in the soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Our finding that exposure to fluoxetine increased boldness matches findings in previous work on sticklebacks (Grécias et al, 2017) and on other fish species (Wong et al, 2013;Ansai et al, 2016;Singer et al, 2016;Sinyakova et al, 2018). Fluoxetine has been shown to also decrease the predator response in sticklebacks (Sebire et al, 2015) and in the fathead minnow (Painter et al, 2009;Weinberger and Klaper, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that exposure to fluoxetine increased boldness matches findings in previous work on sticklebacks (Grécias et al, 2017) and on other fish species (Wong et al, 2013;Ansai et al, 2016;Singer et al, 2016;Sinyakova et al, 2018). Fluoxetine has been shown to also decrease the predator response in sticklebacks (Sebire et al, 2015) and in the fathead minnow (Painter et al, 2009;Weinberger and Klaper, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with that previously observed earlier in zebrafish [ 33 ]. Earlier we showed that an acute (for 3 h) treatment with fluoxetine did not affect the 5-HT level in the brain of zebrafish [ 38 ]. Now we found that prolonged treatment with fluoxetine decreased 5-HT and 5-HIAA levels in the brain of zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Acute [ 35 , 37 , 38 ] or chronic [ 34 , 35 ] treatment with fluoxetine increases time spent near the tank’s surface (“surface dwelling”) in zebrafish. Recently we showed that acute treatment with imipramine also induced “surface dwelling” in zebrafish [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NTT (20 × 20 × 5 cm, made of plexiglass; Open Science, Krasnogorsk, Russia) was divided by an imaginary marker line into top and bottom zones of equal area [ 23 , 29 ]. Trials were recorded with a CNE-CWC1 web camera (Canyon, ASBIS, Limassol, Cyprus) for further analyses, and then they were processed offline using EthoVision XT 11.5 software (Noldus IT, Wageningen, Netherlands) to calculate the total distance traveled (cm), mean and maximum velocity (cm/s), number of freezes (velocity < 2 cm/s), total freezing duration (s), total time spent in the top zone (s), number of entries into the top zone, and latency of the first bottom–top transition (s) [ 23 , 29 , 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%